Padlet Online Discussion in Enhancing Students’ macro Critical Thinking Skills - Mohan, Rathakrishnan; Rahayu, Ahmad; Lee, Jun Choi (Center for Promoting Ideas (CPI), USA., 2017)
Online discussion has become one of the important strategies for the teacher to teach the students to think critically in conveying their ideas and become more proactive and creative.Although there are two types of critical thinking skills: macro and micro critical thinkingbut in this paper,padlet online discussion communication (PODBC) was conducted to examine its effectiveness in enhancing students macro critical thinking.A total of 70 Universiti Utara Malaysia Management Foundation Programme students involved in this experimental research design. The students in treatment class are divided tofew groups. Every group uses back channel padlet online discussion to discuss the topic given. All the group members discuss and write their ideas in padlet. Ideas that are posted in padlet will be displayed in front of the class so that the entire group in the treatment class could see the given ideas. Paul’s model was used to analyze student’s macro critical thinking in padlet online discussion backchannel communication.The finding shows that students who used padlet online discussion backchannel communication have greater macrocritical thinking level than students who do not use back channel.